The importance of nutrition for pediatric liver transplant patients - Pawłowska, Joanna (Clinical and Experimental Hepatology, 2016)
Pediatric liver transplantation has changed the poor prognosis for children with liver failure, some metabolic diseases and liver tumors. With the increase of survival, long-term maintenance has become a priority. Therefore, obtaining appropriate nutrition, physical growth, bone metabolism, endocrine function and psychosocial development has become one of the most important long-term objectives. This article presents an up-to-date review and recommendation of nutrition assessment, both before and after liver transplantation.